2017
DOI: 10.1038/s41598-017-01105-8
|View full text |Cite
|
Sign up to set email alerts
|

As a carrier–transporter for hair follicle reconstitution, platelet-rich plasma promotes proliferation and induction of mouse dermal papilla cells

Abstract: Morphogenesis of hair follicles during development and in hair reconstitution assays involves complex interactions between epithelial cells and dermal papilla cells (DPCs). DPCs may be a source of cells for hair regeneration in alopecia patients. Reconstitution of engineered hair follicles requires in vitro culture of trichogenic cells, a three-dimensional scaffolds, and biomolecular signals. However, DPCs tend to lose their biological activity when cultured as trichogenic cells, and scaffolds currently used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…When Wnt signaling is activated, GSK‐3 is inhibited, and the β‐catenin that enters the cytoplasm is translocated into the nucleus where it initiates the transcription of target genes . In a previous study, we assayed the gene and protein expression of β‐catenin in DPCs treated with 5% activated PRP supernatant and found that β‐catenin expression was upregulated in PRP‐treated DPCs compared with controls . In this study, we found that GSK‐3 expression was lower in cells treated with activated PRP supernatant than in control cells, which suggests that activated PRP supernatant enhanced the hair‐inducing capacity of DPCs by activating the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When Wnt signaling is activated, GSK‐3 is inhibited, and the β‐catenin that enters the cytoplasm is translocated into the nucleus where it initiates the transcription of target genes . In a previous study, we assayed the gene and protein expression of β‐catenin in DPCs treated with 5% activated PRP supernatant and found that β‐catenin expression was upregulated in PRP‐treated DPCs compared with controls . In this study, we found that GSK‐3 expression was lower in cells treated with activated PRP supernatant than in control cells, which suggests that activated PRP supernatant enhanced the hair‐inducing capacity of DPCs by activating the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Normal human scalp hair follicles were obtained during hair follicle transplantation procedures All the follicles were in the anagen phase, and the DPCs were dissociated and cultured as previously described . Briefly, the collagen capsules surrounding the follicle bulbs were removed, the dermal papillae were microdissected from the bulbs and transferred to cell culture in Dulbecco's modified Eagle's medium (DMEM; Gibco, Grand Island, NY, USA) supplemented with 10% (v/v) fetal bovine serum (FBS, Gibco).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a combined approach may favor cellular interactions in vitro, hopefully guiding the development and differentiation of both epithelial and mesenchymal counterparts to form a mature HF. To this end, recent work disclosed an interesting approach using a bioactive scaffold based on platelet‐rich plasma that synergistically combines 3D culture environment with natural release of endogenous growth factors …”
Section: Regenerative Medicine Therapy For Hair Loss: How Far?mentioning
confidence: 99%
“…To this end, recent work disclosed an interesting approach using a bioactive scaffold based on platelet-rich plasma that synergistically combines 3D culture environment with natural release of endogenous growth factors. 71 Envisioning the large-scale production of HF germs needed for a clinical setup, different innovative high-throughput strategies have been conceived, using both mouse and human cells. 3D-printing technology is currently being used in the hair research field to print 3D molds resembling HF microenvironment.…”
Section: Regenerative Medicine Therapy For Hair Loss: How Far?mentioning
confidence: 99%